Interactions Between Academics and the Market - Almeida, Jose Elias Feres de (Advances in Scientific and Applied Accounting, 2024)
The editorial highlights the importance of collaboration between academia and the market. Despite institutional barriers, this interaction benefits both sides: faculty enrich their teaching with practical experiences, and students gain greater opportunities in the job market. Additionally, joint projects generate new research ideas. One alternative is external activities; however, cultural and bureaucratic factors in higher education institutions (HEIs) must be considered in these partnerships. The key takeaway is that a virtuous cycle begins with the first step from both sides toward solidifying this relationship.